Sensitivity and Specificity of Three Measures of Intrinsic Capacity in Older People Aged 80 and Over in Nursing Homes - Ma L; Zheng E; Fang Y; Chen H; Zhou C; Cai S; Luo F; Jiang W; Wang J; Ning X; Tu H; Yin Z (Clinical Interventions in Aging)
Linlin Ma,1,2,* Enjie Zheng,3,* Yi Fang,1 Huixian Chen,1 Chuncong Zhou,4 Shuya Cai,1 Fen Luo,1 Wen Jiang,1 Jialu Wang,1,5 Xiangxiang Ning,6 Haixia Tu,1 Zhiqin Yin1,7 1School of Nursing, Wenzhou Medical University, Wenzhou, Zhejiang, People’s Republic of China; 2The Affiliated People’s Hospital of Ningbo University, Ningbo, Zhejiang, People’s Republic of China; 3The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, People’s Republic of China; 4Nursing Department, Naval Hospital of Eastern Theater, Zhoushan, Zhejiang, People’s Republic of China; 5Department of Nursing, Ningbo No. 6 Hospital, Ningbo, Zhejiang, People’s Republic of China; 6College of Nursing, Ningbo College of Health Sciences, Ningbo, Zhejiang, People’s Republic of China; 7Wenzhou Health Promotion Research Center, Wenzhou, Zhejiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhiqin Yin; Haixia Tu, School of Nursing, Wenzhou Medical University, North Near the Intersection of Zhongxin North Road and Qiuzhen Road, Ouhai District, Wenzhou, Zhejiang, 325035, People’s Republic of China, Tel +8613634269187 ; +8615088969190, Email yzq@wmu.edu.cn; tuhaixia2020@126.comPurpose: Intrinsic capacity (IC), a crucial indicator for the United Nations Decade of Healthy Ageing 2021– 2030, is defined by WHO as the foundation of functional ability, representing the composite of all physical and mental capacities of an individual. IC spans five function domains: Locomotor, psychological, cognitive, vitality, and sensory (including vision and hearing). Accurate IC assessment is vital for effective interventions, yet comparative analyses of these tools are scarce. Consequently, we evaluated the diagnostic accuracy of three IC assessment tools in individuals aged 80 and above—Integrated care for older people (ICOPE) Step 1, ICOPE Step 2, and the Lopez-Ortiz’s IC scoring system.Patients and Methods: This cross-sectional analysis included a total of 475 participants aged ≥ 80 years between July 2023 and January 2024 in 11 nursing homes in Ningbo, Zhejiang Province, China. To assess that included sociodemographic and health-related information alongside the three IC tools. Diagnostic efficacy was gauged using sensitivity, specificity, negative predictive value (NPV), positive predictive value (PPV), accuracy, Youden index, and the area under the curve (AUC).Results: The detection of IC decline exceeded 85% across all methods. Using ICOPE Step 2 as a benchmark, ICOPE Step 1 showed robust performance across four domains of locomotion, psychological, cognitive, and vitality, whereas the Lopez-Ortiz’s IC scoring system was generally ineffective.Conclusion: All three IC assessment methods have limitations. To save resources, ICOPE Step 1 can be considered for direct assessment in non-sensory domains. Conversely, the ICOPE Step 2 and Lopez-Ortiz’s IC scoring systems exhibited overly stringent and lenient thresholds, respectively. At this stage, IC assessment tools cannot balance subjectivity and objectivity; thus, it is recommended that the appropriate tool be selected according to actual application scenarios. Continuous improvement of IC assessment tools remains a requirement for future studies.Keywords: intrinsic capacity, aged 80 years and older, integrated care for older people, tool comparison, sensitivity and specificity, nursing homes